Syntactic Analysis of the Translation of the Interpretation of the Noble Qur’an by Muhammad Taqiuddin Al-Hilali and Muhammad Muhsin Khan - Huriyah Huriyah (Ulumuna, 2014)
Muhammad Taqiuddin al-Hilali and Muhammad Muhsin Khan are distinguished translators of some Islamic books, such as, the interpretation of al-Qur’an, Sahih Al-Bukhari, and Al-Lu’lu’ wa al-Marjan into English. Selecting sūrah al-Qadr as a topic of syntactic analysis, the aim of this paper is to know syntactic rules in English translation used by the translators. The sūrah is selected because it contains important meaning. As an example, its third āyah states that laylah al-Qadr (the night of al-Qadr) is better than a thousand months’; it means that worshipping Allah in that night is better than worshipping Him a thousand months i.e., 83 years and 4 months. Analyzing the syntax of surah al-Qadr, the writer uses the rules of Transformational Grammar (TG).